2006
DOI: 10.1021/jp055060b
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Atom Transfer Energetics:  Assessment of the Effect of Method and Solvent

Abstract: Several density functional methods, the semiempirical methods AM1 and PM3, Hartree-Fock, and Gaussian3 theories were applied to compute the oxygen atom transfer enthalpies for 14 X/XO couples (inorganic and organic systems, charged and neutral species, light and heavy main group element containing molecules). The calculated reaction enthalpies were compared to available experimental data. The G3 method alone was found to perform within the experimental error, while the popular B3LYP and BLYP functionals provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…For the smallest molecules where the G3 methodology is applicable, similar results are obtained at the M05-2X/6-311G(3df,2p) level. Calculated values using the B3LYP functional give worse results as previously shown by Cundari and co-workers 42 giving the worst agreement with the experimental (or G3-calculated) data with the phosphines (Supporting Information, Table S1).…”
Section: ' Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the smallest molecules where the G3 methodology is applicable, similar results are obtained at the M05-2X/6-311G(3df,2p) level. Calculated values using the B3LYP functional give worse results as previously shown by Cundari and co-workers 42 giving the worst agreement with the experimental (or G3-calculated) data with the phosphines (Supporting Information, Table S1).…”
Section: ' Resultsmentioning
confidence: 99%
“…G3 theory is known for delivering chemical accuracy; however, its high computational cost most often give preference to the less computationally demanding DFT methods. Cundari and co-workers have shown that the G3 method performs within the experimental error in calculating the thermochemistry of OAT reactions, while DFT methods such as the popular B3LYP functional provided inadequate results. As can be seen in Table , a good agreement between experimental data and calculated values at the M05-2X/6-311G(3df,2p) level is obtained for all the species studied.…”
Section: Resultsmentioning
confidence: 99%
“…Solvation corrections to the free energy in aqueous and organic media were obtained for the reactants, products, reactant and product hydrated complexes, and transition structures with the CPCM approach at the B3LYP/6-311++G(d,p) level. As the free energy of solvation is highly dependent upon the solute cavity type, we have employed Pauling radii, as implemented in the Gaussian03 package, on the basis of previous results that involved sulfur-containing species. , For each CPCM single-point calculation, three solvents have been considered: water, toluene, and FS-13. While for water and toluene we have employed the default parameters (water, dielectric constant ε = 78.39 and solvent radius r = 1.385 Å; toluene, dielectric constant ε = 2.379 and solvent radius r = 2.820 Å), for the nonstandard FS-13 solvent we have utilized toluene as the predefined solvent with explicitly defined parameters specific for FS-13 (dielectric constant ε = 29.0, solvent radius r = 3.895 Å, density ρ = 0.00404 molecule/Å 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…While there are several studies in the literature which incorporate the effects of solvation into composite methodologies, most include solvation as an additive energetic term at a density functional level of theory (DFT). A 2010 study by Ho and Coote calculated the p K a values for a set of oxicams, nonsteroidal anti-inflammatory drugs (NSAIDs) with analgesic and antipyretic properties . Various DFT methods were compared to the performance of G3MP2(+)-cc gas-phase calculations, with M05-2X yielding the most promising results.…”
Section: Introductionmentioning
confidence: 99%
“…However, solvation effects were accounted for using B3LYP and a smaller basis set with CPCM, COSMO, and SMD continuum solvent models. Similarly, Dinescu et al used the G3 composite method to calculate the free energies of solvation for oxygen transfer reactions in a variety of small systems. In this prior work, the effects of solvation were also included at the B3LYP level with a 6-31++G(2d,2p) basis set, using PCM, CPCM, IEFPCM, and COSMO continuum solvent models.…”
Section: Introductionmentioning
confidence: 99%